Ammonium carbamates as highly active transdermal permeation enhancers with a dual mechanism of action - Novotný, Michal; Klimentová, Jana; Janůšová, Barbora; Palát, Karel; Hrabálek, Alexandr; Vávrová, Kateřina (Journal of controlled release, 2011)
Transdermal permeation enhancers are compounds that temporarily increase drug flux through the skin by interacting with constituents of the stratum corneum. Transkarbam 12 (T12) is a highly active, broad-spectrum, biodegradable enhancer with low toxicity and low dermal irritation. We show here that T12 acts by a dual mechanism of action. The first part of this activity is associated with its ammonium carbamate polar head as shown by its pH-dependent effects on the permeation of two model drugs. Once this ammonium carbamate penetrates into the stratum corneum intercellular lipids, it rapidly decomposes releasing two molecules of protonated dodecyl 6-aminohexanoate (DDEAC) and carbon dioxide. This was observed by thermogravimetric analysis and infrared spectroscopy. This step of T12 action influences drug permeation through lipidic pathways, not through the aqueous pores (polar pathway) as shown by its effects on various model drugs and electrical impedance. Consequently, protonated DDEAC released in the stratum corneum is also an active enhancer. It broadens the scope of T12 action since it is also able to increase permeation of hydrophilic drugs that prefer the pore pathway. Thus, this dual effect of T12 is likely responsible for its favorable properties, which make it a good candidate for prospective clinical use.
Keywords: Aminocaproates; Spectrophotometry, Infrared; Electric Impedance; permeabilita; Sus scrofa; theofylin; elektrická impedance; aplikace kožní; termogravimetrie; fyziologie kůže; Palmitic Acid; Hydrogen-Ion Concentration; aminokapronáty; kůže; kyselina palmitová; hydrokortison; Theophylline; Hydrocortisone; koncentrace vodíkových iontů; Permeability; lipidy; Carbamates; Animals; Thermogravimetry; Aminocaproic Acid; Carbon Dioxide; karbamáty; Adjuvants, Pharmaceutic; Skin; zvířata; kyselina 6-aminokapronová; Skin Physiological Phenomena; kožní absorpce; Skin Absorption; oxid uhličitý; Lipids; adjuvancia farmaceutická; spektrofotometrie infračervená; Epidermis; epidermis; Administration, Cutaneous